Pataka: Media Informasi dalam Kegiatan Mahasiswa - Hasmawati, Hasmawati (Emik, 2024)
In the current era where everything is instantaneous, things can be done using the internet or online media so that something to be done can be done more effectively, such as disseminating information online is easier than disseminating information offline. Social media has become the dominant communication medium used by society and as a medium for obtaining information, including among students. In the midst of the onslaught of online media, offline media, named Pataka, still exists today. This article deals with this. This research using a qualitative approach was carried out in Makassar City between September and December at Hasanuddin University. Those who participated in this research were 10 college students, consisting of three women and seven men, aged between 19 and 21 years, who were recruited using purposive sampling. The findings of this research show that pataka is interpreted in relation to three aspects, namely: pataka as a visual communication tool, sacred media, representation/symbol of student body, and marker for the location of the implementation of students’ body activities. Pataka have various shapes and functions: small square pataka, large square pataka, and rectangular pataka. The small square pataka functions as a marker for activities carried out outside the campus. The large square pataka serves to place the institution's logo. Although large square pataka can be used outside or inside campus, generally large square pataka is used for stage backgrounds. Meanwhile, the rectangular pataka functions as a welcome banner. Even though in this current era the onslaught of technology is so powerful, pataka as an offline medium is still used among college students. The fundamental aspects that underlies why pataka still exists today because pataka has become part of the tradition of a student body in their institutional activities. Apart from that, the existence of pataka is also a symbol of unity and solidarity of student body members.